Alternative Energy from Waste - Esther Kemka (International Journal of Engineering and Management Research, 2019)
Municipal solid waste management is one of the major problems in almost all major cities all over the world. A variety of technologies have been employed to manage the problem of solid waste as well as the conversion of waste to clean energy. The constant rise in the world’s population invariably gives rise to more waste production as well as rise in energy demands which places a strain on already existing energy resources like fossil. Waste in the 21st century is no more seen as ‘waste’ as it were but a resource which can be transformed into various forms and uses like energy. Therefore waste multi-reuse and conversion should be given priority in developing countries, for a better solution of waste control and management. This will not only reduce the ecological and environmental damage caused by pollution, but also reduce the energy demand and consumption and, thus, save primary energy. This paper presents the challenge of waste in the environment and makes a case for the potential of converting this waste to energy. It further discusses six methods of waste to energy conversion, their environmental impacts, merits and demerits of each method and finally gives recommendations for use cases for each method.